A novel DEAH-box helicase 37 mutation associated with differences of sex development - Wan, Yun; Yu, Richeng; Luo, Jianhua; Huang, Ping; Zheng, Xingju; Sun, Liqun; Hu, Kui (Frontiers in Endocrinology, 2023)
Objective To determine the genetic etiology of a family pedigree with two patients affected by differences of sex development (DSD). Methods Assess the clinical characteristics of the patients and achieve exome sequencing results and in vitro functional studies. Results The 15-year-old proband, raised as female, presented with delayed puberty and short stature associated with atypical genitalia. Hormonal profile showed hypergonadotrophic hypogonadism. Imaging studies revealed the absence of a uterus and ovaries. The karyotype confirmed a 46, XY pattern. Her younger brother presented with a micropenis and hypoplastic scrotum with non-palpable testis and hypospadias. Laparoscopic exploration was performed on the younger brother. Streak gonads were found and removed due to the risk of neoplastic transformation. Post-operative histopathology showed the co-existence of Wolffian and Müllerian derivatives. Whole-exome sequencing identified a novel mutation (c.1223C>T, p. Ser408Leu) in the Asp-Glu-Ala-His-box helicase 37 gene, which was found to be deleterious by in silico analysis. Segregation analysis of the variant displayed a sex-limited, autosomal dominant, maternal inheritance pattern. In vitro experiments revealed that the substitution of 408Ser by Leu caused decreased DHX37 expression both at the mRNA and protein levels. Moreover, the β-catenin protein was upregulated, and the p53 protein was unaltered by mutant DHX37. Conclusions We described a novel mutation (c.1223C>T, p. Ser408Leu) of the DHX37 gene associated with a Chinese pedigree consisting of two 46, XY DSD patients. We speculated that the underlying molecular mechanism might involve upregulation of the β-catenin protein.